METHOD OF DETERMINING RELIABILITY PIDSYLENYHSHAROM STALEFIBROBETONU CONCRETE ELEMENTS DURING THE RECONSTRUCTION OF BUILDINGS AND STRUCTURES - and; and (Municipal economy of cities. Series: «Economy science», 2013)
Presented one way to reinforce concrete elements that work on bending, which is building the stretched edge element layer stalefibrobetonu. The dependencies determined for calculating the strength of normal cross section of the beam and integrated to calculate the reliability of the beam for bearing capacity of normal cross section.